Enhancing the productivity of ryegrass at elevated CO2 is dependent on tillering and leaf area development rather than leaf-level photosynthesis. (14th December 2020) - Yiotis, Charilaos; McElwain, Jennifer C; Osborne, Bruce A
Abstract : Variability in ryegrass responses to elevated CO2 shows that biomass stimulation strongly associates with enhancements in leaf area/tillering capacity and is largely unrelated to leaf-level photosynthetic rate. Abstract: Whilst a range of strategies have been proposed for enhancing crop productivity, many recent studies have focused primarily on enhancing leaf photosynthesis under current atmospheric CO2 concentrations. Given that the atmospheric CO2 concentration is likely to increase significantly in the foreseeable future, an alternative/complementary strategy might be to exploit any variability in the enhancement of growth/yield and photosynthesis at higher CO2 concentrations. To explore this, we investigated the responses of a diverse range of wild and cultivated ryegrass genotypes, with contrasting geographical origins, to ambient and elevated CO2 concentrations and examined what genetically tractable plant trait(s) might be targeted by plant breeders for future yield enhancements. We found substantial ~7-fold intraspecific variations in biomass productivity among the different genotypes at both CO2 levels, which were related primarily to differences in tillering/leaf area, with only small differences due to leaf photosynthesis. Interestingly, the ranking of genotypes in terms of their response to both CO2 concentrations was similar. However, as expected, estimates of whole-plant photosynthesis were strongly correlated with plant productivity. Our results suggest that greater yield gains under elevated CO2 are likely through the exploitation of genetic differences in tillering and leaf area rather than focusing solely on improving leaf photosynthesis.